Association of Vitamin D Level and Forced Expiratory Volume in First Second in COPD Patients (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a major cause of morbidity and mortality throughout the world which is preventable as well as treatable disease. In recent years, multiple roles of vitamin D have been highlighted in various diseases. Data on vitamin D status in COPD in Bangladeshi population are still limited. Aim of our study is to see any association between vitamin D level and FEVI (Forced Expiratory Volume in First Second) in COPD patients.Materials and methods: Fifty cases of COPD patients were diagnosed by GOLD (Global Initiative for Chronic Obstructive Lung Disease) criteria included in this study conducted at Medicine Department of Chittagong Medical College Hospital for six months period from April 2018 to September 2018. Serum vitamin D 25-OH level were assessed by enhance chemiluminance method and post-bronchodilator FEV1 was measured in all patients by spirometry.Results: The mean age of patients was 64.50 ± 7.60 years. The mean serum 25-OHD level was 21.69 ± 7.39 ng/ml and mean FEV1 (%) was 20.62 ± 18.80. There was very strong positive correlation present between, serum 25-OHD and FEV1% of predicted. Only 16% of the COPD patients had sufficient vitamin D level, 42% had insufficient and other 42% had deficient vitamin D status.Conclusion: COPD patients with more severe disease tend to have lower serum Vitamin D level.JCMCTA 2019 ; 30 (2) : 22-25